PENYIMPANGAN IMPLIKATUR PERCAKAPAN DALAM HUMOR-HUMOR GUS DUR - Dwi Budiyanto (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2009)
This study aims to describe forms of speech implicature violations in the discourse of Gus Dur’s humors. The data sources were collections of his humors in okezone.com and gusdur.net. The data were analyzed using the descriptive technique involving tabulation, categorization, and inference. The data were selected and categorized on the basis of the maxim violations and then analyzed and inferred in accordance with types and forms of violations from the cooperative and politeness principles. The results show that humorous effects in Gus Dur’s humors are made through the utilization of speech implicature violations. In the cooperative principle, there are violations from the maxims of quantity, quality, relevance, and manner. In the politeness principle, there are violations from maxims of generosity, approbation, and modesty.